2011
DOI: 10.3109/09546634.2011.631979
|View full text |Cite
|
Sign up to set email alerts
|

How psoriasis patients perceive, obtain, and use biologic agents: Survey from an academic medical center

Abstract: The availability of new biologic agents for the treatment of psoriasis provides hope for improved quality of life outcomes. However, the way patients come to use biologics, potential barriers they encounter, and their attitudes towards using these medications are still not well studied. Here, we conducted a survey of 106 psoriasis patients at an academic medical center to discern patient attitudes towards biologics. We found that most patients learn of biologics through their physician and perform follow-up re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…However, in our multivariable regression analyses, we controlled for various confounding factors so that such effects would be minimized and false interpretation could be avoided. Although different adherence measures were applied in other studies, limiting comparability with results from ALIGN, the percentages of patients with PS or CD treated with TNFi monotherapy and combination therapy who reported high adherence based on the MMAS-4 corresponded to the adherence levels for biologics reported in the same IMIDs by other authors [8, 45]. Another limitation is the cross-sectional rather than prospective design of this study.…”
Section: Discussionmentioning
confidence: 88%
“…However, in our multivariable regression analyses, we controlled for various confounding factors so that such effects would be minimized and false interpretation could be avoided. Although different adherence measures were applied in other studies, limiting comparability with results from ALIGN, the percentages of patients with PS or CD treated with TNFi monotherapy and combination therapy who reported high adherence based on the MMAS-4 corresponded to the adherence levels for biologics reported in the same IMIDs by other authors [8, 45]. Another limitation is the cross-sectional rather than prospective design of this study.…”
Section: Discussionmentioning
confidence: 88%
“…A further 22 relevant associated articles were found. Excluding duplications, a total of 52 relevant articles were identified …”
Section: Resultsmentioning
confidence: 99%
“…Most studies in adults report low adherence rates (21.6%‐75%). Four studies found a positive association between treatment adherence and clinical improvement in psoriasis symptoms . Poor adherence to topical therapy is the most common cause of treatment failure.…”
Section: Topical Therapymentioning
confidence: 99%